Novel design of the converter for an active UPS application based on Marx modulator concept with supercapacitors - Pestana, Celso (2019)
A new Marx modulator 4-leg multilevel converter is proposed to replace the well-known 4-leg inverter fed from batteries in Uninterruptible Power Supply (UPS) applications. The novel design concept for the Marx modulator based multilevel converter is presented and described. Each leg uses 2 Marx modulator modules, each one using an Electrochemical Double-Layer Capacitor (EDLC) (also known as supercapacitor (SC)) energy storage bank. The new topology concept enables multilevel operation with five voltage level per phase, allowing high quality voltage and current waveforms, distributed supercapacitor storage and reduction of supercapacitor bank voltage. The proposed converter can operate as UPS or as Active Power Filter (APF), powering non-linear or/and unbalanced loads, while balancing each leg supercapacitor voltage. A control strategy to choose the redundant vector configuration to balance the supercapacitor voltages is explained. Simulation results are presented for a Marx modulator based interactive 40 kVA UPS.